Effect Of Internal Measures Of Service Quality On Business Performance - HJ. DIN, SAARI (2005)
Hotel industry in Penang has a long history since the establishment of E&O Hotel 120 years ago in Penang. Hotel industry and tourism sector is to be seen as symbiotic interrelated. They have played a significant role in transformation of business activities that share the bulk of today’s economy and also account for most of the growth in new jobs in many developed and developing countries. Service quality is a key factor for success in any service industry.